An Exploration Of The Relationship Between Leadership Styles And The Implementation Of Transformation Interventions - J. Naidu (SA Journal of Human Resource Management, 2005)
The objective of this research was to determine whether a relationship exists between the way in which subordinates experience their managers’ leadership styles and the influence of such leadership styles on the implementation of transformation interventions. A two-phase triangulated research design was employed where the qualitative phase preceded the quantitative phase. Ninety six (N = 96) respondents from a mining company participated in the survey. Results indicate a statistical and meaningful correlation between Integrated Leadership styles and transformation interventions but no correlation between Directive Leadership and implementation of transformation interventions.